Diagnosis of Mercurial Teeth in a Possible Case of Congenital Syphilis and Tuberculosis in a 19th Century Child Skeleton. (29th March 2015) - Ioannou, Stella; Henneberg, Maciej; Henneberg, Renata J.; Anson, Timothy
Abstract : Without the presence of " caries sicca, " "sabre shins, " and nodes/expansion of the long bones with superficial cavitation, differential diagnosis of venereal syphilis and tuberculosis (TB) may be difficult as various infections produce similar responses. However, congenital syphilis has distinctive features facilitating a diagnosis. A case study of remains of a juvenile European settler (probably male, 8–10 years old) (B70) buried in the 19th century and excavated in 2000 from the cemetery of the Anglican Church of St. Marys in South Australia is presented. B70 demonstrated that the two diseases might have been present in the same individual, congenital syphilis and TB. Widespread destruction of vertebral bodies and kyphosis-related rib deformations indicate advanced TB. Severe dental hypoplasia is limited to permanent incisors and first molars; there is pitting on the palate, periosteal reaction on the skull vault, and thinned clavicles. Dental signs are not limited to "screwdriver" central incisors and mulberry molars. Apical portions of the crowns of permanent upper, lower, central, and lateral incisors have multiple hypoplastic-disorganized defects; deciduous canines have severely hypoplastic crowns while possibly hypoplastic occlusal surfaces of lower deciduous second molars are largely destroyed by extensive caries. These dental abnormalities resemble teeth affected by mercurial treatment in congenital syphilitic patients as described by Hutchinson.